Hunting as the main technique used to control wild pigs in Brazil - Rosa, Clarissa Alves Da; Wallau, Marcelo Osório; Pedrosa, Felipe [UNESP] (Wiley, 2018)
Wild pigs (Sus scrofa) have expanded their range in Brazil since late 1980s, with reports of damage becoming more frequent in recent years. In 2013, use of lethal methods for wild pig control was legalized by the federal environmental agency. However, several restrictions related to the purchase and transportation of guns and ammunition hamper the ability to evaluate the effectiveness of control measures. Nevertheless, many citizens engaged in wild pig control in Brazil do not officially report their control activities as required by the legislation. Our goal was to characterize the profile of wild pig controllers in Brazil to understand their methods and motivations, estimate the number of wild pigs killed per person per year, and evaluate current regulations regarding their applicability to the situations observed in the field. We formulated and distributed a structured questionnaire distributed in 2014 and 2015 to pig controllers (n = 172), including both hunters and nonhunters. Respondents reported killing 2,389 wild pigs, and killing an average of 17.2 (SE = 24.8) pigs/respondent/year, with male and female pigs killed in the same proportion. Forty percent of respondents were acting illegally. Hunters primarily controlled wild pigs to defend third-party properties. Volunteers provided most of the effort toward controlling wild pigs in Brazil and farmers suffered most of the impacts. Therefore, we believe that adjusting the approach to use of hunting after crop harvest, or implementing an integrated program of hunting and traps placed around crops, could be an important new management tool for reducing wild pig population and crop damage. Further, to enhance wild pig control in Brazil, we recommend incentivizing use of corral traps and cages because such techniques have the greatest effect on reducing wild pig population. © 2018 The Wildlife Society.
Keywords: Brazil; citizen science; feral pig; harvest; Sus scrofa; wild boar